Forest fire occurrence increases the distribution of a scarce forest type in the Mediterranean Basin - Arnan, Xavier; Quevedo, Lídia; Rodrigo, Anselm (Acta Oecologica, 2013)
Here we report how ﬁre recurrence increases the distribution of a scarce forest type in NE Spain that is dominated by the resprouter tree species Arbutus unedo. We used a combination of GIS and ﬁeld surveys to determine the effect of ﬁre and pre-ﬁre vegetation on the appearance of A. unedo forests. In the ﬁeld, we also analyzed the factors that promote ﬁre and lead to the appearance of A. unedo forests. Our results reveal an increased occurrence of A. unedo forests in NE Spain in recent years; this phenomenon was strongly related to ﬁre recurrence and the vegetation type present prior to ﬁre. Most Pinus halepensis forests that burned more than once gave rise to A. unedo forests. Our results indicate that these conversions were related to a reduction in pine density coupled with increases in the density and size of A. unedo trees due to recurrent ﬁres. Given that ﬁres are increasing in number and magnitude in the Mediterranean, we predict a major change in landscape structure and composition at the regional scale
The following values have no corresponding Zotero field: publisher: Elsevier Masson SAS
Keywords: Arbutus unedo; Forest dominance; GIS analysis; Mediterranean; Pinus halepensis; Wildﬁres

Post-fire regeneration of Mediterranean plant communities at a regional scale is dependent on vegetation type and dryness - Arnan, Xavier; Rodrigo, Anselm; Retana, Javier (Journal of Vegetation Science, 2007)
Question: We tested whether (1) the change in composition and structure of whole plant communities after ﬁre is directly related to regeneration of the dominant tree species in the canopy; (2) the change in structure and composition of plant communities several years after ﬁre decreases with the proportion of obligate seeders and (3) the proportion of obligate seeders in plant communities increases with the dryness gradient. Location: Catalonia (NE Spain) Methods: We measured ﬂoristic differences between burned and long-since burned sites in eight vegetation types across a climate gradient. We compared 22 sites burnt in 1994 in paired plots with 22 sites that had not been burnt since the 1940s. In each site we placed plots in burned and long-since burned areas, where we identiﬁed the presence and abundance of all plant species. Results: When the tree canopy recovers, structure and composition of the vegetation also return to the long-since burned community; when tree canopy does not recover, composition of the post-ﬁre community varies compared to the long-since burned one. A higher proportion of obligate seeders in the pre- ﬁre community promotes quicker regeneration of the original community. The proportion of obligate seeders increased along the dryness gradient. Conclusions: Regeneration of plant communities after ﬁre depends on the vegetation type before the ﬁre. Regeneration increases when the dominant tree or shrub species persists after ﬁre and with a higher proportion of obligate seeders in the pre-ﬁre community. The proportion of obligate seeders varies along the dryness gradient, which suggests that vegetation in drier areas (when seeders are more abundant) recovers earlier than in moister areas.
Keywords: climatic gradient; community; nomenclature; obligate seeder; resilience; resprouter; Seeder

Post-fire regeneration of Mediterranean plant communities at a regional scale is dependent on vegetation type and dryness - Arnan, Xavier; Rodrigo, Anselm; Retana, Javier (Journal of Vegetation Science, 2007)
Question: We tested whether (1) the change in composition and structure of whole plant communities after ﬁre is directly related to regeneration of the dominant tree species in the canopy; (2) the change in structure and composition of plant communities several years after ﬁre decreases with the proportion of obligate seeders and (3) the proportion of obligate seeders in plant communities increases with the dryness gradient. Location: Catalonia (NE Spain) Methods: We measured ﬂoristic differences between burned and long-since burned sites in eight vegetation types across a climate gradient. We compared 22 sites burnt in 1994 in paired plots with 22 sites that had not been burnt since the 1940s. In each site we placed plots in burned and long-since burned areas, where we identiﬁed the presence and abundance of all plant species. Results: When the tree canopy recovers, structure and composition of the vegetation also return to the long-since burned community; when tree canopy does not recover, composition of the post-ﬁre community varies compared to the long-since burned one. A higher proportion of obligate seeders in the pre- ﬁre community promotes quicker regeneration of the original community. The proportion of obligate seeders increased along the dryness gradient. Conclusions: Regeneration of plant communities after ﬁre depends on the vegetation type before the ﬁre. Regeneration increases when the dominant tree or shrub species persists after ﬁre and with a higher proportion of obligate seeders in the pre-ﬁre community. The proportion of obligate seeders varies along the dryness gradient, which suggests that vegetation in drier areas (when seeders are more abundant) recovers earlier than in moister areas.
Keywords: climatic gradient; community; nomenclature; obligate seeder; resilience; resprouter; Seeder

Post-fire recovery of Mediterranean ground ant communities follows vegetation and dryness gradients - Arnan, Xavier; Rodrigo, Anselm; Retana, Javier (Journal of Biogeography, 2006)
Aim In the Mediterranean Basin, the main forest communities vary in their ability to recover after ﬁre. In this study we analyse the effects of ﬁre on ant communities occurring in various vegetation types distributed along a geographical gradient in the western Mediterranean region. Location The study was carried out in burned and unburned habitats of 22 sites corresponding to eight vegetation types distributed along a gradient of dryness throughout Catalonia (north-east Spain). Methods We placed ﬁve pairs of plots (one plot located in the burned area and the second one placed in the unburned margin) per site. We compared ant communities in these unburned and burned plot types 8 years after ﬁre using pitfall traps. Traps were set out in mid-May and mid-July. We analysed the structure and composition of ant communities in the burned and unburned areas of these vegetation types using anova tests, correspondence analysis (CA) and linear regression. Results The resilience of ant communities varies with vegetation type. Ant communities in forests with high resilience also recover rapidly after ﬁre, while those in forests that do not recover after ﬁre show the lowest resilience. Species richness does not depend on burning or vegetation type. The resilience of these Mediterranean ant communities to ﬁre is related to the environmental characteristics of the region where they live. Accordingly, differences between burned and unburned habitats are smaller for ant communities in areas with higher water deﬁcit in summer than for those in moister ones. Main conclusions The structure and composition of ant communities after ﬁre depends on the level of direct mortality caused by the ﬁre. It affects ant species differently, as determined by the habitats used for nesting and foraging. The reestablishment of vegetation cover depends on forest composition before the ﬁre. As vegetation cover determines resource and microhabitat availability and competitive relationships among species, forest composition before the ﬁre also affects post-ﬁre recovery of ant communities to the medium-term. Finally, ant communities living in drier areas recover more quickly after ﬁre than those living in moister ones. This pattern might be because in areas with higher water deﬁcit there are more species characteristic of open environments, which are habitats similar to those generated after ﬁre.
Keywords: Ants; diversity; dryness gradient; forest type; Mediterranean communities; post-ﬁre recovery; resilience; Species richness; ﬁre

Post-fire recovery of Mediterranean ground ant communities follows vegetation and dryness gradients - Arnan, Xavier; Rodrigo, Anselm; Retana, Javier (Journal of Biogeography, 2006)
Aim In the Mediterranean Basin, the main forest communities vary in their ability to recover after ﬁre. In this study we analyse the effects of ﬁre on ant communities occurring in various vegetation types distributed along a geographical gradient in the western Mediterranean region. Location The study was carried out in burned and unburned habitats of 22 sites corresponding to eight vegetation types distributed along a gradient of dryness throughout Catalonia (north-east Spain). Methods We placed ﬁve pairs of plots (one plot located in the burned area and the second one placed in the unburned margin) per site. We compared ant communities in these unburned and burned plot types 8 years after ﬁre using pitfall traps. Traps were set out in mid-May and mid-July. We analysed the structure and composition of ant communities in the burned and unburned areas of these vegetation types using anova tests, correspondence analysis (CA) and linear regression. Results The resilience of ant communities varies with vegetation type. Ant communities in forests with high resilience also recover rapidly after ﬁre, while those in forests that do not recover after ﬁre show the lowest resilience. Species richness does not depend on burning or vegetation type. The resilience of these Mediterranean ant communities to ﬁre is related to the environmental characteristics of the region where they live. Accordingly, differences between burned and unburned habitats are smaller for ant communities in areas with higher water deﬁcit in summer than for those in moister ones. Main conclusions The structure and composition of ant communities after ﬁre depends on the level of direct mortality caused by the ﬁre. It affects ant species differently, as determined by the habitats used for nesting and foraging. The reestablishment of vegetation cover depends on forest composition before the ﬁre. As vegetation cover determines resource and microhabitat availability and competitive relationships among species, forest composition before the ﬁre also affects post-ﬁre recovery of ant communities to the medium-term. Finally, ant communities living in drier areas recover more quickly after ﬁre than those living in moister ones. This pattern might be because in areas with higher water deﬁcit there are more species characteristic of open environments, which are habitats similar to those generated after ﬁre.
Keywords: Ants; diversity; dryness gradient; forest type; Mediterranean communities; post-ﬁre recovery; resilience; Species richness; ﬁre